Peran Justice Collaborator dalam Kasus Tindak Pidana Pembunuhan Berencana di Indonesia - Laksmana, Indra Surya (Proceedings Series on Social Sciences & Humanities, 2024)
Justice collaborators are seen as having a strategic role in bringing to light a criminal incident, but in their development justice collaborators still have pros and cons. Justice collaborator itself can be understood as a witness to a perpetrator who works together to reveal the true facts in a particular criminal act and Justice Collaborator basically has the meaning of giving a term to someone who commits a crime who collaborates with law enforcement officials to reveal the veil of a crime they know about. This justice collaborator is also included in Law 13/2014 concerning the Second Amendment to Law 13/2006 concerning Protection of Witnesses and Victims. Justice collaborator protection is a right inherent in witnesses and victims who assist in investigations in criminal cases, especially in the crime of premeditated murder. However, the protection of justice collaborators, especially in premeditated murder, is not regulated comprehensively by law, so there is a legal vacuum.